STORY OF PALAH TEMPLE IN EAST JAVA BATIK VISUALIZATION - Putri, Talisa Fasya Laksita; Indarti, Indarti (Universitas Negeri Yogyakarta, 2025)
Folktales are stories that are told for generations among the people of a region or country. Folklore often serves as a means to convey cultural values, morals, and traditional knowledge from one generation to the next. The purpose of this research is to describe the process of designing batik motifs using the idea of the Palah Temple story as an alternative to East Javanese batik. The research method uses the Double Diamond Model design research method. The Double Diamond Model consists of four stages: Discover, Define, Develop, and Deliver. In the initial stage, the design direction of the batik motif was determined by exploring sources of ideas to be used as a mood board. In the second stage, the researcher develops the moodboard by stylizing the motif development. The third stage is preparing the stylization of the batik motif development by preparing the motif composition. This research has yielded two themes and six developments of batik motifs. The fourth stage involves selecting the best motif to be realized as a long batik cloth prototype, measuring 250 x 115 cm, with the theme